On Stability and Convergence for Discrete-Discontinuous Finite Element Method (Journal of Computational Mathematics, 1984)
In this paper, we deal with the discrete-discontinuous finite element method for solving the time-dependent neutron transport equation in two-dimensional planar geometry. Its stability and convergence are proved. The numerical results are given. Compared with SN method it is of higher accuracy and superconvergence.